After Auschwitz the difficult legacies of the GDR - Heitzer, Enrico 1977-; Jander, Martin 1955-; Kahane, Anetta 1954-; Poutrus, Patrice G. 1961- (Berghahn, 2021)
Intro -- After Auschwitz -- Contents -- Illustrations -- Introduction - New Perspectives on the GDR: A Plea for a Paradigm Shift -- Part I - German Democratic Republic -- Chapter 1 - The Loyalty Trap: Wolfgang Steinitz and the Generation of GDR-Founding Fathers and Mothers -- Chapter 2 - The Effects of a Taboo: Jews and Antisemitism in the GDR -- Chapter 3 - Divided City-Shared Memory? Dealing with the Nazi Past in East and West Berlin from 1948 to 1961 -- Chapter 4 - The GDR and Opposition from the Right: A Plea for Broader Perspectives -- Chapter 5 - The GDR's Judgment against Hans Globke: On the Conviction of the Nazi Lawyer and Head of the Federal Chancellery under Konrad Adenauer by the Supreme Court of the GDR in the Summer of 1963 -- Chapter 6 - Might through Morality? Some Comments on Antifascism in the GDR -- Chapter 7 - Toward a Sociology of Intelligence Agents: The GDR Foreign Intelligence Service as an Example -- Chapter 8 - At War with Israel: Anti-Zionism in East Germany from the 1960s to the 1980s -- Chapter 9 - Holocaust Lite? Fiction in Works by Christa Wolf and Fred Wander -- Chapter 10 - The Stigma of "Asociality" in the GDR: Reconstructing the Language of Marginalization -- Chapter 11 - Lesbians and Gays in the GDR: Self-Organizing, Politics of Remembrance, Discrimination, and Public Silencing -- Chapter 12 - Have We Learned the "Right" Lessons from History? Antigypsyism and How the GDR Dealt with Sinti and Roma -- Chapter 13 - The GDR People's Chamber Declaration of 12 April 1990: Ending the "Universalization" of the Holocaust -- Part II - Federal Republic of Germany -- Chapter 14 - Understanding Silence: On an Ongoing Search for People, Things, and Connections Not Really Unknown -- Chapter 15 - "A Reassessment of European History?" Developments, Trends, and Problems of a Culture of Remembrance of Europe